Planificación y valoración patrimonial de los usos sociales, rituales y actos festivos de la Cultura Puruwá, de las Parroquias Rurales del circuito Sur del Cantón Riobamba - Villagómez Zambrano, Cristina Belén (2019)
Planning and heritage value of social uses, rituals and festive events of Puruwa culture, at rural parishes of the southern circuit of the Riobamba Canton, was a study developed taking into account the multiculturalism that the canton preserves, but as time went by, the evolution of technology has caused that new generations abandon their beliefs, homes and, most all, the tradition of carrying out their festivities, so this causes lack of practice and loss of value to social uses, rituals and festive acts of their culture. In order to determine how the planning allows the patrimonial valuation of the social uses, rituals and festive acts of the Puruwa culture, of the rural parishes of the southern circuit of the Riobamba Canton, they have been fulfilled by identifying the manifestations with the registration of the INPC files, and taking into account the information given by the presidents and technicians of the Rural Decentralized Autonomous Governments and the Tourism Directorate of the GADM Riobamba as well as the development of the SWOT diagnosis, complying prioritization process for obtaining strategies that, were applicable as a proposal in this research, framed towards the new generations, since they are the ones who have forgotten or ignore the activities carried out in each of the festivities. As a conclusion we can say that in order to give a heritage value to each of the social uses, rituals and festive events are linked to significant events at different human life stages, especially in the history and memory of their communities so planning is needed by each of the public actors that maintain competencies and must comply with current legal regulations.